1997
DOI: 10.1021/bc960066c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Novel [125I]Neonicotinoid Photoaffinity Probe for theDrosophilaNicotinic Acetylcholine Receptor

Abstract: The insect nicotinic acetylcholine receptor (nAChR) is the target for the major insecticide imidacloprid (IMI) and for the first candidate photoaffinity probe described here. Addition to 1-[(6-chloro-3-pyridinyl)methyl]-4,5-dihydro-2-nitromethylene-1H-imidazolidine (the nitromethylene analog of the nitroimine IMI) of formaldehyde and any one of several primary amines is known to give hexahydro-8-nitroimidazo[1,2-c]pyrimidine derivatives. These imidazopyrimidines with a wide range of N-substituents were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…In 1988, Nihon Tokushu Noyaku Seizo Company synthesized a series of cis-configuration compounds and some exhibited high insecticidal activities against insect pests, such as the green leafhopper N. bipunctatus (Shiokawa et al, 1988). In 1992, Bayer reported a dicyclic neonicotinoid analogue and fixed nitro group in cis-position, which showed obvious biological activity and exhibited high affinity on nAChRs from Musca domestica or Drosophila melanogaster (Latli et al, 1997). In a previous study, we have also found some potential neonicotinoids with cis-configuration (Tian et al, 2007;Shao et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…In 1988, Nihon Tokushu Noyaku Seizo Company synthesized a series of cis-configuration compounds and some exhibited high insecticidal activities against insect pests, such as the green leafhopper N. bipunctatus (Shiokawa et al, 1988). In 1992, Bayer reported a dicyclic neonicotinoid analogue and fixed nitro group in cis-position, which showed obvious biological activity and exhibited high affinity on nAChRs from Musca domestica or Drosophila melanogaster (Latli et al, 1997). In a previous study, we have also found some potential neonicotinoids with cis-configuration (Tian et al, 2007;Shao et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Casida's group developed a neonicotinoid-agarose matrix (33) and successfully applied it to isolate three putative subunits of the native Drosophila and Musca nAChR from head membrane preparations (Fig. 11) [36,37]. Photoaffmity labelling is another approach to access and characterize the ligand-binding site environment in the receptor.…”
Section: Neonicotinoid Molecules For the Elucidation Of Nachr Structurementioning
confidence: 99%
“…Table 6 compares the toxicity LD 50 values of nitro and desnitro compounds to housefly and mouse. Actually desnitro imidacloprid (37) and the analogous imine (38) show strong toxicity to mouse, whereas the original insecticides (9,10) show the high selectivity to the housefly [45]. At present neonicotinoids and related compounds including 7V-unsubstituted imines will be a focus in the intensive search for potential agents for neuropathic disorders, cognitive enhancement and analgesia.…”
Section: Neonicotinoids As Mammalian Nachr Agentsmentioning
confidence: 99%
“…Given that CH-IMI has been reported as a potential new insecticide, a series of neonicotinoid insecticides that use CH-IMI as a basic unit have been rapidly developed in recent years. These insecticides possess novel structures and various modes of action compared with traditional insecticides, including hexahydronitroimidazopyrimidines [4-6], some of which are shown as compounds I to IV (Figure 1) [7-12]. Neonicotinoid insecticides are known to act agonistically and show high selectivity to insect nicotinic acetylcholine receptors; they are also relatively safe toward mammals and aquatic species [13-15].…”
Section: Introductionmentioning
confidence: 99%